2011
DOI: 10.1007/s10535-011-0191-7
|View full text |Cite
|
Sign up to set email alerts
|

Callus induction and plant regeneration from immature embryos of Brachypodium distachyon with different chromosome numbers

Abstract: The paper reports the in vitro cultivation of two commercial lines and 23 wild populations (with 10, 20 and 30 chromosomes) of Brachypodium distachyon. Callus induction was assayed on Murashige and Skoog medium containing 1 mg dm -3 2,4-dichlorophenoxyacetic acid (2,4-D) with 30 g dm -3 of sucrose (MSs) or maltose (MSm). No significant differences were seen between the two media with respect to callus induction. Calli were transferred to MSm medium without 2,4-D but containing 0.1 mg dm -3 of 6-benzylaminopuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
0
7
0
5
Order By: Relevance
“…Although it was demonstrated that a high-efficiency transformation callus can also be obtained from whole seeds, immature embryos are the most suitable explant for callus induction in Brachypodium [8, 9]. These embryos are highly susceptible to the stimulatory conditions of an in vitro culture, which results in the first callus clusters being observed after only a week [10]. Such a callus is of a high quality and regeneration potential, which makes it a preferred target for genetic transformation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although it was demonstrated that a high-efficiency transformation callus can also be obtained from whole seeds, immature embryos are the most suitable explant for callus induction in Brachypodium [8, 9]. These embryos are highly susceptible to the stimulatory conditions of an in vitro culture, which results in the first callus clusters being observed after only a week [10]. Such a callus is of a high quality and regeneration potential, which makes it a preferred target for genetic transformation [7].…”
Section: Introductionmentioning
confidence: 99%
“…A la vista de los resultados obtenidos en un ensayo previo de cultivo in vitro limitado a dos medios de cultivo (Hammami et al, 2011a), se eligieron seis poblaciones con diferentes números cromosómicos. A partir de estos materiales se ha llevado a cabo un es- tudio sobre la influencia de los diferentes niveles cromosómicos de las poblaciones analizadas, el tipo y la concentración de la auxina añadida a los medios (2,4-D, Dicamba o Piclorán) y la interacción 'medio x población'.…”
Section: Discussionunclassified
“…Thus, two populations of 2n = 30 chromosomes, Bd238 and Bd341 were those of the best behavior, whereas the populations Bd160 and Zulema' with 2n = 10 chromosomes, showed the lowest response. yon como modelo de cereales de climas templados, se han llevado a cabo estudios de respuesta al cultivo in vitro en diferentes poblaciones (Bablak et al, 1995;Draper et al, 2001Hammami et al, 2011a.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations